Thermally induced phase change glass coating material as well as preparation method and application thereof

Through the doping and composite technology of VO2 nanoparticles, a heat -phase -coated material of low phase change temperature and high -light transparency have been prepared, which solves the lack of thermal management of automotive window materials, and achieves efficient infrared infrared Light regulation and the super stability of materials.

CN119330604APending Publication Date: 2025-01-21HONG KONG PRODUCTIVITY COUNCIL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411552426.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing automotive window materials perform poorly in thermal management, resulting in inefficient temperature regulation in the vehicle and increased fuel consumption and battery load. The high phase transition temperature of vanadium dioxide (VO2) thermochromic materials and the lattice defects that are prone to occur during preparation limit their application in automotive windows.

Method used

Through the doping and composite technology of VO2 nanoparticles, a low -phase variable temperature (40-45 ° C), high light transparency (70-80 %), and high -durable thermal phase -changing glass coating materials. This material solves the problem with the substrate from the volume change during the VO2 phase change through multi -layer covering and the introduction of the elastic medium layer, and achieves transparent effect by introducing the silicon dioxide of low refractive index material.

Benefits of technology

It is possible to improve the infrared light regulation performance, isolate solar heat, reduce automobile energy consumption while ensuring high visible light transmittance, and improve the oxidation resistance and environmental stability of VO2 particles to ensure the super stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330604A_ABST
    Figure CN119330604A_ABST
Patent Text Reader

Abstract

The invention relates to a thermally induced phase change glass coating material as well as a preparation method and application thereof. The method comprises the following steps: grinding and mixing V2O5 and MoO3 powder, melting, preserving heat, adding into ionized water, stirring until the V2O5 and MoO3 powder is dissolved and dispersed, and standing to obtain a mixed solution containing VO2 nanoparticles and Mo ions; the preparation method comprises the following steps: adding tetraethoxysilane into absolute ethyl alcohol, stirring, adding ammonia water while stirring, and hydrolyzing to obtain a solution containing SiO2 nanoparticles; adding deionized water into the mixed solution and the solution containing the SiO2 nanoparticles, and carrying out hydrothermal reaction, annealing and drying to obtain precursor sol of which the surfaces of VO2 particles are coated with the SiO2 transparent material; dipping a clean SiO2 glass substrate into the precursor sol, and then pulling the SiO2 glass substrate from the precursor sol; and after pulling, the SiO2 glass substrate stays in the air, and is dried to obtain the thermally induced phase change glass coating material with the VO2 / Mo composite film. According to the invention, the problems of low solar energy regulation rate and low weather resistance of glass can be solved, so that intelligent, dynamic and accurate regulation and control of solar energy are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of glass coatings, and in particular to a thermoinduced phase change glass coating material and a preparation method and application thereof. Background Art

[0002] Energy and environmental issues are severe challenges facing countries around the world. Transportation energy consumption is listed as one of the three major "energy consumers" and is highly valued by countries around the world. Data shows that automobile energy consumption accounts for about 20% to 40% of the total social energy consumption in developing countries. Glass windows are the main heat exchange channel between the car body and the external environment, accounting for about 50% of the heat flowing into or out of the car. Therefore, energy saving of doors and windows is a key link in automobile energy saving, so there is an urgent need to develop energy-saving glass.

[0003] Temperature control methods such as air conditioning and heating are one of the main sources of automobile energy consumption. Especially in southern my country, which is a hot summer and warm winter area, the summer sunshine is strong, and the energy consumption of automobile cooling is very high. Against the background of global warming, resource depletion and environmental degradation, the rational use of existing non-renewable energy and the development and utilization of renewable energy occupy an equally important position. Traditional automobile window materials perform poorly in thermal management, resulting in inefficient temperature regulation in the car, which increases fuel consumption and battery load (for electric vehicles). Therefore, developing automobile window materials that can automatically adjust optical and thermal properties according to external temperature changes, and using the light and heat response characteristics of the material that are closely related to the natural environment to build an intelligent temperature control energy-saving system is a trend in the field of energy conservation, and is also an ideal choice for achieving temperature control in other fields such as automobiles and aerospace aircraft.

[0004] Thermochromic materials can change their optical properties with temperature and are ideal for realizing smart car windows. Vanadium dioxide (VO2) is a typical thermochromic material that undergoes a metal-insulator phase transition at about 68°C, thereby changing its optical transmittance. VO2 behaves as a metallic phase at high temperatures, with low visible light transmittance and high infrared reflectivity; it behaves as an insulating phase at low temperatures, with high visible light transmittance and low infrared reflectivity. Although VO2 has excellent thermochromic properties, its high phase transition temperature (about 68°C) limits its practical application in automotive windows. In addition, VO2 films are prone to lattice defects during the preparation process, resulting in a decrease in optical properties. To overcome these problems, researchers have tried to reduce the phase transition temperature of VO2 by doping with other elements (such as tungsten, molybdenum, etc.) while improving its optical and thermal properties. At the same time, embedding VO2 nanoparticles into a glass matrix can effectively improve the mechanical strength and durability of the material while maintaining its excellent thermochromic properties. Through the sol-gel technique, the uniform dispersion of VO2 nanoparticles in the glass matrix can be achieved, thereby obtaining a composite material with high optical transparency and stability. In addition, by rationally designing the composition and structure of the composite material, its thermochromic properties can be further optimized, enabling it to achieve phase transition at a lower temperature. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a thermoinduced phase change glass coating material and a preparation method and application thereof, with the goal of preparing an ultra-stable phase change material, realizing multi-layer coating of vanadium oxide materials, introducing an elastic medium layer to solve the problem of separation from the substrate caused by volume change during the phase change of vanadium dioxide, introducing low refractive index material silicon dioxide to achieve an anti-reflection effect, and at the same time limiting the volume effect during the phase change of vanadium dioxide to increase stability.

[0006] In order to achieve the above object, the present invention provides a method for preparing a thermotropic phase change glass coating material, comprising the following steps:

[0007] S1, grinding and mixing V2O5 powder and MoO3 powder, melting, keeping warm, adding into ionized water and stirring until they are completely dissolved and dispersed, and then standing to obtain a mixed solution containing VO2 nanoparticles and Mo ions;

[0008] S2, adding tetraethyl orthosilicate to anhydrous ethanol and stirring, adding ammonia water while stirring, and obtaining a solution containing SiO2 nanoparticles through hydrolysis reaction; adding deionized water to the mixed solution containing VO2 nanoparticles and Mo ions and the solution containing SiO2 nanoparticles obtained in step S1 for hydrothermal reaction, annealing and drying to obtain a precursor sol of SiO2 transparent material coated on the surface of VO2 particles;

[0009] S3, immersing a clean SiO2 glass substrate into the precursor sol obtained in step S2, and then pulling the SiO2 glass substrate from the precursor sol; after pulling, the SiO2 glass substrate is left in the air, and then dried to obtain a thermotropic phase change glass coating material having a VO2 / Mo composite thin film.

[0010] Preferably, in step S1, the molar ratio of the V2O5 powder to the MoO3 powder is 2.5-3.0.

[0011] Preferably, in step S1, the melting temperature is 700-800°C and the holding time is 30-40 minutes.

[0012] Preferably, in step S2, the volume of the anhydrous ethanol accounts for 70% to 80% of the total volume of the reaction solution, and the reaction solution consists of anhydrous ethanol, tetraethyl orthosilicate and ammonia water.

[0013] Preferably, in step S2, the concentration of the tetraethyl orthosilicate is 0.2M-1.0M, and the volume ratio of the tetraethyl orthosilicate based on the total amount of the reaction solution is 20%-50%.

[0014] Preferably, in step S2, the mass percentage concentration of the ammonia water is 25%, and its volume is 2-5 times the volume of tetraethyl orthosilicate.

[0015] Preferably, in step S2, the temperature of the hydrolysis reaction is 20-25° C., and the time is 2 hours to 10 hours.

[0016] Preferably, in step S2, the particle size of the SiO2 nanoparticles in the solution containing SiO2 nanoparticles is 100nm-500nm.

[0017] Preferably, in step S2, the temperature of the hydrothermal reaction is 100-200° C., and the time is 10-24 h.

[0018] Preferably, in step S2, the annealing temperature is 500-600° C. and the time is 1-2 h.

[0019] Preferably, in step S2, the drying temperature is 80-100° C. and the drying time is 10-30 min.

[0020] Preferably, in step S2, in the precursor sol of SiO2 transparent material for coating the surface of the VO2 particles, the mass proportion of VO2 is between 20% and 30%, the mass proportion of SiO2 is between 70% and 80%, and the refractive index of SiO2 is 1.4-1.5.

[0021] Preferably, in step S2, the surface of the VO2 particles is coated with SiO2 transparent material to form a core-shell structure including a SiO2 shell layer, the average particle size of the core-shell structure is between 100-300 nm, and the thickness of the SiO2 shell layer is between 5-50 nm.

[0022] Preferably, in step S3, the purity of the SiO2 glass substrate is >99%.

[0023] Preferably, in step S3, the pulling speed is 1500-1800 μm / s, the immersion time is 100-120 s, and the residence time is 100-120 s.

[0024] Preferably, in step S3, the drying temperature is 80-100° C. and the drying time is 10-30 min.

[0025] Preferably, in step S3, the size of VO2 particles in the VO2 / Mo composite film is 100-500nm, and the thickness of the VO2 / Mo composite film is 500nm-3μm.

[0026] In order to achieve the above object, the present invention further provides a thermotropic phase change glass coating material, wherein the thermotropic phase change glass coating material has a VO2 / Mo composite film.

[0027] Preferably, the size of VO2 particles in the VO2 / Mo composite film is 100-500nm, and the thickness of the VO2 / Mo composite film is 500nm-3μm.

[0028] Preferably, the thermotropic phase change glass coating material is prepared by the above method.

[0029] In order to achieve the above object, the present invention also provides an energy-saving automobile window material, which uses the above-mentioned thermotropic phase change glass coating material.

[0030] Preferably, the phase change temperature of the energy-saving automobile window material is 40-45° C., and the visible light transmittance is 70-80%.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The thermochromic glass material of the present invention overcomes the limitations of existing materials through the doping and compounding technology of VO2 nanoparticles, and provides an energy-saving automobile window material with low phase transition temperature (40-45°C), high optical transparency (70-80%) and excellent durability, which has broad application prospects and significant market competitive advantages;

[0033] The present invention can solve the problems of low solar regulation rate and weather resistance of glass, so as to realize intelligent dynamic and precise regulation of solar energy; when the external temperature is higher than the phase change temperature, the film layer can improve the infrared light regulation performance (>40%) and isolate the heat of the sun while ensuring high visible light transmittance (70% to 80%); in a low temperature environment (range of 0 to 40°C), the film layer can ensure the intake of heat energy through solar light regulation, so as to realize an energy-saving mode of keeping the car warm in winter and cool in summer;

[0034] The present invention ensures the excellent phase change characteristics of VO2 while obtaining high visible light transmittance (70% to 80%), and the infrared light regulation performance is greater than 40%; at the same time, the oxidation resistance and environmental stability of VO2 are enhanced, and the problem of VO2 oxidation and deterioration in the process of embedding VO2 film and in the actual working application environment is solved, and the oxidation resistance temperature of VO2 particles in oxygen is increased to 600°C, ensuring good contact between vanadium oxide and the matrix and isolation from the external environment, and realizing the ultra-stability of vanadium dioxide phase change materials;

[0035] The present invention aims to prepare an ultra-stable phase change material, realizes multi-layer coating of vanadium oxide materials, introduces an elastic medium layer to solve the problem of separation from the matrix caused by volume change during the phase change of vanadium dioxide, introduces low refractive index material silicon dioxide to achieve an anti-reflection effect, and at the same time limits the volume effect during the phase change of vanadium dioxide, increases stability, and overcomes the problem of separation of the material from the matrix to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. The drawings in the following description are only some embodiments of the present invention, wherein:

[0037] Figure 1 VO2 morphology structure diagram according to an embodiment of the present invention.

[0038] Figure 2 4 is a curve diagram showing the change of infrared transmittance of the VO2 composite material with temperature according to an embodiment of the present invention. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. The structures, proportions, sizes, etc. shown in the accompanying drawings are only used to match the contents disclosed in the specification so that people familiar with this technology can understand and read them. They are not used to limit the limiting conditions that the present invention can be implemented, so they have no technical substantive significance. Any structural modification, change in proportional relationship or adjustment of size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects that the present invention can produce and the purposes that can be achieved.

[0040] Interface construction is the key to improve the stability of VO2 nanoparticles in the present invention. The present invention intends to effectively inhibit oxygen diffusion and prevent the failure caused by the solid phase reaction between materials at the interface by forming a stable interface on the basis of early exploration and theoretical analysis. For this reason, the present invention selects SiO2 and other transparent coating materials, and adopts Stober method and sol-gel method to form a dense multilayer composite shell structure on the surface of VO2 nanoparticles. SiO2 and other materials have high stability and corrosion resistance. The shell structure can effectively isolate the contact of phase change materials with oxygen, acid and alkali substances in the environment, thereby improving weather resistance and stability. In addition, SiO2 and other materials all belong to oxides, do not react chemically with VO2, and are difficult to diffuse at the interface, which can ensure the stability of the interface. Vanadium dioxide will undergo obvious volume changes during the phase change process, and repeated expansion and contraction cause the separation of vanadium oxide and transparent matrix. Reducing dimming performance is another important reason for its failure. How to reduce the volume effect through the construction of composite structure is another key scientific problem solved by the present invention.

[0041] To this end, some embodiments of the present invention provide a method for preparing a thermotropic phase change glass coating material, comprising the following steps:

[0042] Step 1, reference Figure 1, VO2 nanoparticles were prepared by controlled oxidation technology to achieve controllable size, morphology and distribution. The vanadium dioxide film was prepared by sol-gel method, and its phase transition temperature was adjusted by Mo ion doping. V2O5 powder and MoO3 powder were weighed at a molar ratio of 2.5-3.0, poured into an agate mortar for full grinding, so that the particles were more refined and mixed evenly. The purpose of Mo ion doping is to adjust the phase transition temperature of vanadium dioxide. If the molar ratio between V2O5 powder and MoO3 powder is lower than 2.5, it may not be enough to effectively reduce the phase transition temperature, thereby affecting the application performance of the material; while the molar ratio between V2O5 powder and MoO3 powder is higher than 3.0, the low doping amount of MoO3 powder may lead to uneven distribution of Mo ions in the material, affecting the uniformity and stability of the film. Then it was poured into a small crucible, placed in a muffle furnace and heated to 700-800℃ to melt it. The melting treatment at 700-800℃ can promote the crystallization of particles and ensure the improvement of phase transition behavior and mechanical properties of VO2 nanoparticles and films. A treatment temperature below 700°C may form impure phases or low-quality particles, and may even cause the formation of VO2 to fail, thereby reducing the functionality and phase change properties of the material. A temperature above 800°C may cause excessive sintering of the particles, forming larger agglomerations, reducing the specific surface area of ​​the material, thereby reducing the phase change activity and affecting its phase change properties. Keep it warm for 30-40 minutes, take it out and pour it into 200ml-300ml deionized water and stir it quickly. After it is completely dissolved and dispersed, let it stand for 1-2 hours to obtain a mixed solution containing VO2 nanoparticles and Mo ions; if it is less than 30 minutes, insufficient insulation time may lead to incomplete reaction, affecting the quality and performance of subsequent sols. If it is greater than 40 minutes, too long insulation time may cause excessive agglomeration of particles during the cooling process, thereby reducing the dispersion and uniformity of the particles and affecting the quality of the final film. If the volume of deionized water is insufficient (<200ml), the solution concentration may be too high, increasing the interaction between particles, causing aggregation and precipitation, and affecting the uniformity of the material. If the volume of deionized water is too large (>300ml), the concentration of the target may be too low, reducing the effectiveness of the material and the difficulty of subsequent processing. If the standing time is insufficient (<1 hour), the particles may not be fully dispersed, affecting the consistency and distribution of the particle size, and there may be unprecipitated impurities that affect the quality of the final product. Too long a standing time (>2 hours) may cause the particles to settle to the bottom, forming particle accumulation, resulting in phase separation or uneven characteristics, affecting subsequent properties and functions.

[0043] Step 2: Use the Stober method, hydrothermal symbiosis method and subsequent annealing to coat the surface of VO2 particles with SiO2 transparent material, and complete the construction of the core-shell structure of VO2 and transparent material. The addition of SiO2 can improve the hardness and toughness of the material, achieve the effect of anti-reflection, and at the same time limit the volume effect during the phase change of vanadium dioxide, increase stability, and overcome the problem of separation between the material and the matrix. The combination of the Stober method and the hydrothermal symbiosis method is to continue hydrothermal treatment on the SiO2 particles prepared by the Stober method to achieve uniform coating of VO2 particles and the formation of a core-shell structure. Specifically, the steps of the Stober method are as follows: 1) Take a dry beaker and add an appropriate amount of anhydrous ethanol (its volume accounts for 70% to 80% of the total volume of the Stober reaction solution) as a solvent and reaction medium to promote hydrolysis and polycondensation reactions; 2) Slowly add tetraethyl orthosilicate (concentration of 0.2M to 1.0M, volume ratio of 20%-50% based on the total volume of the reaction solution) to the anhydrous ethanol, and stir evenly to ensure that the tetraethyl orthosilicate is completely dissolved; 3) While stirring, slowly add ammonia water. The mass percentage concentration of ammonia water is 25%, and its volume is 2 to 5 times the volume of tetraethyl orthosilicate. Ammonia water will increase the pH value of the reaction system to 9-11, promoting the hydrolysis of tetraethyl orthosilicate. The reaction is carried out at room temperature (20-25°C), the reaction time is 2 hours to 10 hours, and a solution containing SiO2 nanoparticles is obtained. The longer the reaction time, the larger the particle size of SiO2 formed. The Stober method can be used to prepare SiO2 particles with uniform particle size, the particle size of SiO2 particles is between 100nm-500nm, and the prepared SiO2 has high purity (>99%) and good transparency, which helps to maintain the optical properties of VO2 particles. The steps of the hydrothermal symbiosis method are as follows: transfer the mixed solution containing VO2 nanoparticles and Mo ions obtained in step 1 and the solution containing SiO2 nanoparticles obtained above to a hydrothermal reactor, add 200ml-300ml of deionized water, and maintain an appropriate reaction temperature (100-200℃) and reaction time (10-24h). If the deionized water is less than 200ml, the high concentration of reactants may cause the particles to aggregate and become uneven, affecting the formation of the core-shell structure and the dispersibility of the particles. If the deionized water is higher than 300ml, the excess water will dilute the reactants, reduce the reaction rate, and may cause uneven growth of SiO2, thereby affecting the coating quality of VO2. The reaction temperature is lower than 100℃. Too low temperature will lead to slow reaction rate, SiO2 may not be able to effectively cover VO2 particles, and the generated core-shell structure is incomplete, affecting the material performance. The reaction temperature is higher than 200℃. Too high temperature may cause phase change of VO2, thereby changing the optical and electrical properties of the material. Too high temperature may also cause degradation or sintering of the material, causing the particles to cluster and no longer have the desired core-shell structure.If the reaction time is less than 10 hours, insufficient reaction time will lead to incomplete growth of SiO2, which may make it difficult to form a stable core-shell structure, resulting in weakening of the core-shell interface. If the reaction time is higher than 24 hours, too long a reaction time may lead to overreaction of the material, and the SiO2 layer may become too thick, affecting the performance of the particles, and causing the shape and size of the VO2 particles to change, resulting in agglomeration. The Stober method combined with the hydrothermal co-growth method can form a consistent and uniform SiO2 coating layer on the surface of VO2 particles (size see step 2) to ensure the consistency of material performance. The subsequent annealing temperature is 500-600℃, and the annealing time is 1-2h. After annealing, the sample is placed in an oven at a temperature of 80-100℃ and dried for 10-30min to obtain a precursor sol of SiO2 transparent material coated on the surface of VO2 particles. The annealing process is mainly used to promote the bonding between SiO2 and VO2, help form a stable core-shell structure, and improve the crystal structure and phase change properties of the material. If the annealing temperature is lower than 500℃, the SiO2 layer may not be fully bonded, resulting in poor adhesion and affecting the coating effect. If the annealing temperature is higher than 600℃, the VO2 particles may begin to dissolve or change structure, affecting the stability of the crystal phase. If the annealing time is lower than 1h, SiO2 fails to react completely, resulting in an uneven coating layer, affecting the optical and thermal properties. If the annealing time is higher than 2h, the material may oxidize or degrade, affecting its long-term stability and performance. If the drying temperature is lower than 80℃, the solvent is not completely removed, which may cause the sample to decompose or impurities to exist in subsequent processing. If the drying temperature is higher than 100℃, the SiO2 layer may crack or delaminate, affecting the optical transparency and mechanical properties. If the drying time is lower than 10min, too much solvent may remain, resulting in unstable performance of the final product. If the drying time is higher than 30min, the material may be over-dried, resulting in surface roughness or morphological changes. In terms of improving the uniformity of the coating thickness, the present invention continuously changes the stirring direction and the substrate placement direction during the coating process to ensure that the solution is in full contact with the particle surface in all directions, thereby achieving a uniform coating effect, realizing the coating of the SiO2 transparent material on the surface of the VO2 particles, and completing the construction of the core-shell structure of VO2 and the transparent material. Among them, the mass proportion of VO2 is between 20%-30%, the mass proportion of SiO2 is between 70%-80%, and the refractive index of the SiO2 is 1.4-1.5. If the refractive index is lower than 1.4, it may cause too low light transmittance, affect the light transmission effect of the glass, and produce reflection or even distortion effects. If it is higher than 1.5, it may increase reflection loss, thereby reducing light transmittance. In addition, a higher refractive index may also have an adverse effect on the mechanical properties of the phase change material, resulting in increased brittleness, thereby affecting the toughness and stability of the overall material. The average particle size of the resulting core-shell structure is between 100-300nm, and the thickness of the SiO2 shell is between 50-500nm.

[0044] Step three, use high-purity (purity>99%) SiO2 glass as the coating substrate, put it in acetone and anhydrous ethanol for ultrasonic cleaning for 30min-60min, then put it in a dilute hydrochloric acid solution (20wt%) for ultrasonic cleaning for 1-1.5h, take it out and rinse it with deionized water, and blow it dry with nitrogen for later use.

[0045] Step 4, take the precursor sol obtained in step 2, and use a coating puller to prepare a VO2 / SiO2 composite film. Fix the cleaned coating substrate (5cm*5cm) on the bracket of the coating puller to ensure that its position is stable. Adjust the pulling speed to 1500-1800μm / s to ensure accurate speed control of the equipment. Pour the precursor sol into the coating tank to ensure that the amount of sol in the tank is sufficient to cover the substrate. Under the control of the puller, slowly immerse the coating substrate in the precursor sol to start dipping, and the dipping time is set to 100-120 seconds. During the dipping process, ensure that the sol is evenly coated on the surface of the substrate. After the dipping is completed, start the puller to pull the coating substrate out of the precursor sol at a set speed (1500-1800μm / s). During the pulling process, ensure that the substrate is in uniform contact with the precursor sol to form a uniform film. After the pulling is completed, the substrate is left in the air for a residence time of 100-120 seconds to ensure that the film is self-dried in the air. The pulling speed and immersion time directly affect the thickness of the deposited film. A lower pulling speed / more immersion time allows more precursor sol to be deposited on the substrate surface, resulting in a thicker film. On the contrary, a higher pulling speed / less immersion time often results in a thinner film. Insufficient residence time (<100s) may result in the failure of the solvent to completely evaporate, resulting in bubbles or unevenness on the film surface, affecting the optical and electrical properties of the film. Excessive residence time (>120s) may cause the film surface to dry too quickly, forming an uneven surface structure, and may even cause cracks or peeling. After the pulling is completed once, the material is placed in an oven at a temperature of 80-100°C and dried for 10-30 minutes to obtain a thermotropic phase change glass coating material having a VO2 / Mo composite film; the VO2 particle size in the VO2 / Mo composite film is controlled to be 100-500nm, and the thickness of the VO2 / Mo composite film is 500nm-3μm, so as to realize the controllable preparation of the VO2 particle array film. Through the above steps, the VO2 / Mo composite film can maintain a light transmittance of 80%-90% in the visible light range (400-700nm) and a light transmittance of 40%-60% in the near infrared region (700-1100nm).

[0046] The above-mentioned thermo-induced phase change glass coating material with VO2 / Mo composite film can be used to prepare energy-saving automobile window materials. The phase change temperature of the energy-saving automobile window material is 40-45°C, and the visible light transmittance is 70-80%.

[0047] The present invention is further described below in conjunction with specific embodiments.

[0048] Example 1

[0049] This embodiment provides a method for preparing a thermotropic phase change glass coating material, comprising the following steps:

[0050] (1) Preparation of vanadium dioxide thin film by sol-gel method: V2O5 powder and MoO3 powder were weighed in a molar ratio of 11:4, poured into an agate mortar and ground thoroughly, then poured into a small crucible, placed in a muffle furnace and heated to 800°C to melt it, kept warm for 30 minutes, and then quickly taken out and poured into 200 ml of deionized water and stirred rapidly. After it was completely dissolved and dispersed, it was allowed to stand for 1 hour to obtain a mixed solution containing VO2 nanoparticles and Mo ions;

[0051] (2) The Stober method and hydrothermal co-growth method were combined with subsequent annealing (temperature was 600°C) for 2 hours. After annealing, the sample was placed in an oven at 80°C for 30 minutes to achieve the coating of SiO2 transparent material on the surface of the VO2 particles, completing the construction of the core-shell structure of VO2 and the transparent material, and finally completing the mosaic structure. Specifically, the steps of the Stober method are as follows: 1) take a dry beaker and add an appropriate amount of anhydrous ethanol, the volume of which accounts for 80% of the total volume of the Stober reaction solution; 2) slowly add tetraethyl orthosilicate (the concentration is 0.5M, and the volume ratio is 30% based on the total amount of the Stober reaction solution) to the ethanol, and stir evenly to ensure that the tetraethyl orthosilicate is completely dissolved; 3) while stirring, slowly add ammonia water, the mass percentage concentration of ammonia water is 25%, and the volume is twice that of tetraethyl orthosilicate. The ammonia water will increase the pH value of the reaction system to 10. The reaction is carried out at room temperature (25°C) and the reaction time is 2 hours to obtain a solution containing SiO2 nanoparticles. The SiO2 nanoparticles are between 100nm-500nm, and the prepared SiO2 has a high purity (99%) and good transparency. The steps of the hydrothermal symbiosis method are as follows: transfer the mixed solution containing VO2 nanoparticles and Mo ions obtained in step 1 and the solution containing SiO2 nanoparticles obtained above to a hydrothermal reactor, add 300 ml of deionized water, and perform a hydrothermal reaction at 100°C for 10 hours. The subsequent annealing temperature is 600°C and the annealing time is 2 hours. After annealing, the sample is placed in an oven at 80°C and dried for 30 minutes to obtain a precursor sol of SiO2 transparent material coated on the surface of VO2 particles; wherein the mass ratio of VO2 is 30%, the mass ratio of SiO2 is 70%, and the refractive index of SiO2 is 1.4. The average particle size of the obtained core-shell structure is 200nm, and the thickness of the SiO2 shell is 200nm.

[0052] (3) High-purity (purity 99%) SiO2 glass was used as the coating substrate, which was ultrasonically cleaned in acetone and anhydrous ethanol for 30 minutes, and then ultrasonically cleaned in a dilute hydrochloric acid solution (mass fraction 20%) for 1 hour. After being taken out, it was rinsed with deionized water and dried with nitrogen for later use; the cleaned coating substrate (5cm*5cm) was fixed on the bracket of the coating puller, and the pulling speed was adjusted to 1500μm / s. The precursor sol obtained in step 2) was poured into the coating tank to ensure that the amount of sol in the tank was sufficient to cover the substrate. Under the control of the puller, the coating substrate was slowly immersed in the precursor sol to start immersion. The immersion time was set to 100s. The immersion was completed. Then, the pulling machine is started to pull the coated substrate out of the precursor sol at 1500μm / s. After the pulling is completed, the substrate is kept in the air for 100s; after the pulling is completed, it is placed in an oven at 80°C and dried for 30min to obtain a thermotropic phase change glass coating material with a VO2 / Mo composite film; the size of VO2 particles in the VO2 / Mo composite film is controlled at 200nm, the thickness of the VO2 / Mo composite film is 1μm, and the VO2 / Mo film has an average transmittance of 80% in the visible light range (400-700nm), and an average transmittance of 50% in the near-infrared region (700-1100nm).

[0053] The above-mentioned thermotropic phase change glass coating material with VO2 / Mo composite film can be used to prepare energy-saving automobile window materials with high stability. The phase change temperature of the energy-saving automobile window material is 40°C and the average visible light transmittance is 80%.

[0054] Example 2

[0055] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the molar ratio of V2O5 powder to MoO3 powder is 2.5, and the remaining steps and parameters are the same as those in embodiment 1.

[0056] In the thermotropic phase change glass coating material with VO2 / Mo composite film of this embodiment, the size of VO2 particles in the VO2 / Mo composite film is controlled at 300nm, the thickness of the VO2 / Mo composite film is 1.2μm, and the VO2 / Mo film has an average transmittance of 85% in the visible light range (400-700nm) and an average transmittance of 55% in the near-infrared region (700-1100nm).

[0057] The above-mentioned thermotropic phase change glass coating material with VO2 / Mo composite film can be used to prepare energy-saving automobile window materials with high stability. The phase change temperature of the energy-saving automobile window material is 45°C and the average visible light transmittance is 75%.

[0058] Example 3

[0059] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the molar ratio of V2O5 powder to MoO3 powder is 3.0, and the remaining steps and parameters are the same as those in embodiment 1.

[0060] In the thermotropic phase change glass coating material with VO2 / Mo composite film of this embodiment, the size of VO2 particles in the VO2 / Mo composite film is controlled at 350nm, the thickness of the VO2 / Mo composite film is 1.5μm, and the VO2 / Mo film has an average transmittance of 90% in the visible light range (400-700nm) and an average transmittance of 60% in the near-infrared region (700-1100nm).

[0061] The above-mentioned thermotropic phase change glass coating material with VO2 / Mo composite film can be used to prepare energy-saving automobile window materials with high stability. The phase change temperature of the energy-saving automobile window material is 42°C and the average visible light transmittance is 70%.

[0062] Comparative Example 1

[0063] The difference between this comparative example and Example 1 is that in step (1) of this comparative example, the molar ratio of V2O5 powder to MoO3 powder is 2.0, and the remaining steps and parameters are the same as Example 1.

[0064] In the thermotropic phase change glass coating material with VO2 / Mo composite film of this comparative example, the size of VO2 particles in the VO2 / Mo composite film is controlled at 300nm, the thickness of the VO2 / Mo composite film is 1.2μm, and the VO2 / Mo film has an average transmittance of 75% in the visible light range (400-700nm) and an average transmittance of 35% in the near-infrared region (700-1100nm).

[0065] Comparative Example 2

[0066] The difference between this comparative example and Example 1 is that in step (1) of this comparative example, the molar ratio of V2O5 powder to MoO3 powder is 3.5, and the remaining steps and parameters are the same as Example 1.

[0067] In the thermotropic phase change glass coating material with VO2 / Mo composite film of this comparative example, the size of VO2 particles in the VO2 / Mo composite film is controlled at 300nm, the thickness of the VO2 / Mo composite film is 1.2μm, and the VO2 / Mo film has an average transmittance of 77% in the visible light range (400-700nm) and an average transmittance of 36% in the near-infrared region (700-1100nm).

[0068] Figure 1 This is the VO2 morphology structure according to Example 1 of the present invention. Figure 1 It can be seen that the VO2 particle size is between 100nm and 500nm, and the morphology is spherical or rod-shaped. These nanoparticles have a large specific surface area, which helps to improve the phase change rate and thermal response sensitivity.

[0069] Figure 2 : is the curve of the infrared transmittance of the VO2 composite material according to Example 1 of the present invention as a function of temperature. Figure 2 As can be seen in Figure 1, the transmittance changes significantly when the temperature approaches about 40°C. Below this temperature range, the transmittance is relatively high, indicating that the material allows a lot of radiation to pass through. When the temperature exceeds this threshold, the transmittance drops sharply.

[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a thermotropic phase change glass coating material, characterized in that: The steps include: S1, grinding and mixing V2O5 powder and MoO3 powder, melting, keeping warm, adding into ionized water and stirring until they are completely dissolved and dispersed, and then standing to obtain a mixed solution containing VO2 nanoparticles and Mo ions; S2, adding tetraethyl orthosilicate to anhydrous ethanol and stirring, adding ammonia water while stirring, and obtaining a solution containing SiO2 nanoparticles through hydrolysis reaction; adding deionized water to the mixed solution containing VO2 nanoparticles and Mo ions and the solution containing SiO2 nanoparticles obtained in step S1 for hydrothermal reaction, annealing and drying to obtain a precursor sol of SiO2 transparent material coated on the surface of VO2 particles; S3, immersing a clean SiO2 glass substrate into the precursor sol obtained in step S2, and then pulling the SiO2 glass substrate from the precursor sol; after pulling, the SiO2 glass substrate is left in the air, and then dried to obtain a thermotropic phase change glass coating material having a VO2 / Mo composite thin film.

2. The method for preparing the thermotropic phase change glass coating material according to claim 1, characterized in that: In step S1, the molar ratio of the V2O5 powder to the MoO3 powder is 2.5-3.0; the melting temperature is 700-800°C, and the insulation time is 30-40 minutes.

3. The method for preparing the thermotropic phase change glass coating material according to claim 1, characterized in that: In step S2, the volume of the anhydrous ethanol accounts for 70% to 80% of the total volume of the reaction solution, and the reaction solution is composed of anhydrous ethanol, tetraethyl orthosilicate and ammonia water; the concentration of the tetraethyl orthosilicate is 0.2M-1.0M, and the volume ratio of the tetraethyl orthosilicate based on the total amount of the reaction solution is 20%-50%; the mass percentage concentration of the ammonia water is 25%, and its volume is 2-5 times the volume of the tetraethyl orthosilicate; the temperature of the hydrolysis reaction is 20-25°C, and the time is 2 hours-10 hours; the particle size of the SiO2 nanoparticles in the solution containing SiO2 nanoparticles is 100nm-500nm; the temperature of the hydrothermal reaction is 100-200°C, and the time is 10-24h; the temperature of the annealing is 500-600°C, and the time is 1-2h; the temperature of the drying is 80-100°C, and the time is 10-30min.

4. The method for preparing the thermotropic phase change glass coating material according to claim 1, characterized in that: In step S2, in the precursor sol of SiO2 transparent material coating the surface of the VO2 particles, the mass proportion of VO2 is between 20%-30%, the mass proportion of SiO2 is between 70%-80%, and the refractive index of SiO2 is 1.4-1.5; the surface of the VO2 particles is coated with SiO2 transparent material to form a shell-core structure including a SiO2 shell layer, the average particle size of the shell-core structure is between 100-300nm, and the thickness of the SiO2 shell layer is between 5-50nm.

5. The method for preparing the thermotropic phase change glass coating material according to claim 1, characterized in that: In step S3, the purity of the SiO2 glass substrate is >99%; the pulling speed is 1500-1800 μm / s, the immersion time is 100-120 s, and the residence time is 100-120 s; the drying temperature is 80-100°C and the time is 10-30 min.

6. The method for preparing the thermotropic phase change glass coating material according to claim 1, characterized in that: In step S3, the size of VO2 particles in the VO2 / Mo composite film is 100-500nm, and the thickness of the VO2 / Mo composite film is 500nm-3μm.

7. A thermotropic phase change glass coating material, characterized in that: The thermo-induced phase change glass coating material comprises a VO2 / Mo composite film; the size of VO2 particles in the VO2 / Mo composite film is 100-500nm, and the thickness of the VO2 / Mo composite film is 500nm-3μm.

8. The thermotropic phase change glass coating material according to claim 7, characterized in that: The thermotropic phase change glass coating material is prepared by the method described in any one of 1-6.

9. An energy-saving automobile window material, characterized in that: The energy-saving automobile window material adopts the thermotropic phase change glass coating material according to claim 7 or 8.

10. The energy-saving automobile window material according to claim 9, characterized in that: The energy-saving automobile window material has a phase change temperature of 40 to 45° C. and a visible light transmittance of 70 to 80%.